Sensorless Control of a Single-Phase AC–DC Boost Converter Without Measuring Input Voltage and Current - Tavan, Mehdi; Sabahi, Kamran; Shahparasti, Mahdi; Hajizadeh, Amin; Soltani, Mohsen; Savaghebi, Mehdi (IEEE, 2023)
It is well-known that the accurate measurement of input voltage and current, as the feedforward and feedback terms, plays a crucial role in the nonlinear controller design for power factor compensation of an AC-DC boost converter. This paper addresses the problem of the simultaneous estimation of the input voltage and current from the output voltage in a full-bridge AC-DC boost converter. In the lossless model of the system, those variables are unobservable from the output voltage when the control input is zero. To overcome this, the system dynamics are immersed in a proper form by a new filtered transformation. The phase and amplitude of the input voltage, along with the input current, are globally estimated from the output voltage by a fifth-dimensional estimator. Unlike some existing results, the stability of the proposed estimator does not rely on a priori knowledge about the parasitic resistances and is guaranteed exponentially under the persistence of excitation conditions on the control signal. An application of the proposed estimator is presented in conjunction with a dynamic controller to form a sensorless control algorithm that does not require any sensor on the input side and controls the system only by the feedback from the output voltage. Processor-in-the-loop (PIL) studies conducted by OPAL-RT OP 5700 are used to assess the performances of the proposed estimator and controller.
Keywords: AC–DC power converters; adaptive estimator; immersion and invariance technique; Lyapunov stability; fi=Sähkötekniikka|en=Electrical Engineering|